Living in Temporary Ponds Loading Giant Genomes: The Neotropical Annual Killifish Genus Austrolebias as New Outstanding Evolutionary Model - García, Graciela; Gutiérrez, Verónica; Ríos, Néstor (Frontiers in Genetics, 2022)
Annual killifish includes a short-lived and amazing vertebrates inhabiting temporary ponds exposed to an extremely variable environment in its short lifespan in South America and Africa, leading to the death of the entire adult population during the dry season. Austrolebias is a specious genus of the family Rivulidae, with ~58 currently recognized species, extensively distributed in temperate Neotropical region. Herein, we reviewed different aspects of the evolutionary biology with emphasis in the genome dynamic linked to burst speciation process in this genus. Austrolebias constitutes an excellent model to study the genomic evolutionary processes underlying speciation events, since in all the species of this genus analyzed so far, share an unusually large genome size, with an average DNA content of 5.95 ± 0.45 picograms per diploid cell (mean C-value of about 2.98 pg). The drastic nuclear DNA–increasing would be associated to considerable proportion of transposable elements (TEs) found in the Austrolebias genomes. The genomic proportion of the moderately repetitive DNA in A. charrua genome represents approximately twice (45%) of the repetitive components of the highly related sympatric and syntopic rivulinae taxon Cynopoecilus melanotaenia (25%), as well as from other rivulids and actinopterygian fish. These events could explain the great genome instability, the high genetic diversity, chromosome variability as well as the morphological diversity in species of Austrolebias.Thus, species of this genus represent new model systems linking different evolutionary process: drastic genome increase, massive TEs genomic representation, high chromosome instability, occurrence of natural hybridization between sister species and burst speciation events.